2020
DOI: 10.7717/peerj.10025
|View full text |Cite
|
Sign up to set email alerts
|

The lemur baseline: how lemurs compare to monkeys and apes in the Primate Cognition Test Battery

Abstract: Primates have relatively larger brains than other mammals even though brain tissue is energetically costly. Comparative studies of variation in cognitive skills allow testing of evolutionary hypotheses addressing socioecological factors driving the evolution of primate brain size. However, data on cognitive abilities for meaningful interspecific comparisons are only available for haplorhine primates (great apes, Old- and New World monkeys) although strepsirrhine primates (lemurs and lorises) serve as the best … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…Finally, most of the cognitive tests were not explicitly designed to have any functional relevance in terms of sociality or variation in social traits, so that a correlation with performance scores is unlikely. Hence, to address the relative importance of either ecological or social factors driving the evolution of brain size, comprehensive cognitive test batteries addressing both sets of factors are required (Shaw and Schmelz 2017;Völter et al 2018;Fichtel et al 2020).…”
Section: Variation In Cognitive Performance In Relation To Group Sizementioning
confidence: 99%
“…Finally, most of the cognitive tests were not explicitly designed to have any functional relevance in terms of sociality or variation in social traits, so that a correlation with performance scores is unlikely. Hence, to address the relative importance of either ecological or social factors driving the evolution of brain size, comprehensive cognitive test batteries addressing both sets of factors are required (Shaw and Schmelz 2017;Völter et al 2018;Fichtel et al 2020).…”
Section: Variation In Cognitive Performance In Relation To Group Sizementioning
confidence: 99%
“…For the first time reported about plants by Debono (2016Debono ( , 2018 [12,17] who adapted the concept of plasticity (Table 1) he developed [29,30] to their behavior (i.e. developing a mesological plasticity), that highlights the plant body anchored in the soil (Table 1).…”
Section: The Mesological Plasticity Of Plantsmentioning
confidence: 99%
“…If this hypothesis was adopted, added to the sensible vs sensitive nature recently admitted by the scientific community about the sensory system of plants, it would constitute a big step in our classification of the living kingdoms and in the modeling of sensory perception modes [34]. This could help solve the apparent conundrum of cognitive scales disproportionate to the size of the brain of animals like birds (recent works show that the delta observed between the small size of the brains of birds and their high cognitive abilities are probably due to a high density of neurons: see Olkowicz et al 2019) [28] or lemurs having relatively small brains for primates (Fichtel et al, 2020) [29], without mentioning one of the great puzzles of contemporary science, i.e. the unicellular unclassifiable organisms such as the Polycephalum physarum that are able to execute high cognitive tasks without brain.…”
Section: Plant 'Intelligence' and Sensitiveness: Why Is All This Possmentioning
confidence: 99%
“…Therefore, it is suggested that their vision plays a minor or no role in some social tasks, such as species or mate recognition (e.g., Braune et al, 2008;Gomez et al, 2012;Kollikowski et al, 2019). Nevertheless, there is evidence from laboratory studies that visual stimuli consisting of two horizontally paired circles, resembling a pair of eyes, can trigger submissive gaze aversion in the gray mouse lemur (Coss, 1978) and that mouse lemurs can use visuosocial cues from a human experimenter to spontaneously solve tasks in a lemur version of the primate cognitive test battery (Fichtel et al, 2020). Finally, there is some evidence that vision supports predator detection and recognition in mouse lemurs (e.g., Rahlfs & Fichtel, 2010;Zimmermann et al, 2000).…”
Section: Introductionmentioning
confidence: 99%